"It's a walk of shame": Experiences of unintended pregnancy and abortion among sexual- and gender-minoritized females in urban India. Issue 1 (July 2021) - Bowling, Jessamyn; Simmons, Megan; Blekfeld-Sztraky, Donna; Bartelt, Elizabeth; Dodge, Brian; Sundarraman, Vikram; Lakshmi, Brindaa; Herbenick, Debby
Background: Unintended pregnancy and safe abortion access in India remain critical public health concerns. The health of sexual- and gender-minoritized females (SGMF; those assigned female at birth and identify as other than heterosexual and/or as other than cisgender women) in India is understudied. Aim: We examined experiences of unintended pregnancy and abortion among SGMF individuals in urban India. Methods: We used focus group discussions ( n = 8 individuals in two groups) and interviews ( n = 20) with SGMF individuals. Data were collected in December 2017. Transcripts were analyzed using a priori thematic analysis and then open thematic analysis in Dedoose online software. Results: Nine participants experienced or suspected they had unintended pregnancies. Pregnancy circumstances were mostly due to sex without using a barrier method. Participants discussed using traditional methods to induce abortion or changing their approach to contraception. Social support was often lacking, though partners were supportive of abortion choices. Participants reported stigma and surveillance from family, friends, providers, and community members. Conclusion: These findings highlight the effects of stigma in relation to abortion and unintended pregnancy on health and relationships.